Curriculumul intercultural: orientări, principii, resurse [Articol] - Chiriac, Argentina; Guțu, Vladimir (CEP USM, 2007)
The intercultural education represents a transcultural and methodological provocation for the teachers and the creators of the curricula. The intercultural phenomenon represents a very precious resource that can be appreciated in the educational sphere. The intercultural education actually is an education of interpersonal relations that involves the members of different cultures. The realization of the intercultural relation is based on the importance of the processes of interaction, collaboration, opening, changing, and knowledge.
Keywords: intercultural education; educaţia interculturală